Unemployment benefits : should there be a compulsory Federal standard? - Becker, Joseph M. (Washington : American Enterprise Institute, 1980)
This study examines one proposal to increase federal control of the states- specifically, the proposal to impose a federal standard on state unemployment insurance benefits.
Includes bibliographical references.
rpm 17/04/2018
Loans
Keywords: Unemployment insurance